2017
DOI: 10.3390/sports5030047
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Motivation and Barriers to Physical Activity among Active and Inactive Australian Adults

Abstract: Physical inactivity is a major global public health issue associated with a range of chronic disease outcomes. As such, the underlying motivation and barriers to whether or not an individual engages in physical activity is of critical public health importance. This study examines the National Heart Foundation of Australia Heart Week Survey conducted in March 2015. A total of 894 (40% female) Australian adults aged 25–54 years completed the survey, including items relating to motivation and barriers to being ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
124
2
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(150 citation statements)
references
References 37 publications
15
124
2
9
Order By: Relevance
“…However, both men and women talked about being motivated to be active for health reasons. This has some similarities with previous research which suggest women's motivations focus more on appearance and physical condition [8,10,37]. However, this research importantly found that the forest environment was seen by some of the women as a space where they are not judged on appearance and where they can feel more comfortable exercising and less self-conscious.…”
Section: Discussionsupporting
confidence: 80%
“…However, both men and women talked about being motivated to be active for health reasons. This has some similarities with previous research which suggest women's motivations focus more on appearance and physical condition [8,10,37]. However, this research importantly found that the forest environment was seen by some of the women as a space where they are not judged on appearance and where they can feel more comfortable exercising and less self-conscious.…”
Section: Discussionsupporting
confidence: 80%
“…The most prevalent barriers to physical activity reported by inactive adults were 1) the absence of interest or unwillingness to make an effort, 2) tiredness at work, and 3) lack of time, which are common barriers reported by other studies [7,24,30,52]. However, the proportion of adults reporting these barriers is more than two times higher in the current study than in the study conducted in Poland [30].…”
Section: Discussioncontrasting
confidence: 60%
“…These findings are supported by several national studies comprising the whole population of one country and examining the perceiving barriers to physical activity. In Australia, physically inactive adults reported lack of time (50%), lack of enjoyment (43.9%), and preferring to do other things (42.9%) as the main obstacles to being physically active [24]. Finnish adults also outlined lack of time (55.6% in men; 57.5% in women) as the main barrier, followed by a lack of motivation (25.6% in men; 21.6% in women), lack of company to be active with (15.9% in men; 18.8% in women), and high expenses (9.4% in men; 9.6% in women) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the finding that daily PA seems to be negatively associated with BWU, a significantly higher proportion of daily active females reported weight unhappiness compared to males. Considering findings from Western countries (De Bruin, Woertman, Bakker, & Oudejans, 2008;Hoare, Stavreski, Jennings, & Kingwell, 2017), this may suggest that body weight regulation through exercise among adolescent females may be a stronger motivating factor for daily activity than for males.…”
Section: Physical Activity and Body Imagementioning
confidence: 96%